Microsatellite and mitochondrial DNA based genetic diversity analysis of a lesser known Chitarangi sheep of north-western India - MISHRA, A K; JAIN, ANAND; SINGH, S; AHLAWAT, S; SHARMA, R (The Indian Journal of Animal Sciences, 2020)
Microsatellite and mitochondrial DNA based genetic characterization of Chitarangi sheep population inhabiting Fazilka and Muktsar districts of Punjab and Sriganganagar district and adjoining areas of Rajasthan was carried out, and genetic diversity measures were analysed. High estimates of allele diversity (9.875±0.641) and gene diversity (0.712±0.027) were observed across the population. A significant positive FIS (0.096±0.031) value suggested a deficiency in the number of heterozygotes in Chitarangi sheep. The population revealed presence of substantial genetic diversity and the typical L-type distribution of allelic frequencies indicated the absence of any recent bottlenecks in Chitarangi sheep and no mode shift was detected in this population. Majority of haplotypes identified through mitochondrial DNA based analysis of Chitarangi sheep grouped with major haplogroup A that is predominantly of Asian origin. The genetic characterization of Chitarangi sheep will help in devising suitable strategies for its genetic improvement, management and recognition at National level.